A review of abdominoplasty technique with reduced dissection and fixation with Baroudi sutures - Julio Alberto Soncini; Ricardo Baroudi (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: A retrospective study was carried out on 500 abdominoplasties with lower pubic transverse incision combined with liposuction, performed from 2007 to 2014. In all cases, the dissection of the abdominal skin flap was restricted, with adhesion sutures applied throughout the dissected regions. The use of vacuum suction drains was also evaluated. In 33% of cases, these drains were not used, but no signs of seroma were detected, proving the efficacy of adhesion sutures. METHODS: In all abdominoplasties, the access route was the lower transverse pubic region extended up to the level of the anterior superior iliac spines bilaterally, combined with liposuction in the adjacent regions. After the dissection, plication of the rectus muscles, and resection of excess skin, adhesion sutures were applied throughout the dissected regions. RESULTS: The systematic use of adhesion sutures was efficient, without the need to use drains, given the absence of seroma in all cases. CONCLUSION: In lower pubic transverse abdominoplasty, limited dissection of the cutaneous flap extended up to the xiphoid, combined with adhesion sutures and liposuction, avoided the use of vacuum drains; no seroma developed, and the results were good.